Business document image processing - Qian, Guo Yu (2009)
In an office environment, a large amount of information is manipulated in the form of business documents. Currently, two types of documents are commonly used for business communication. They are paper documents (for example letters, memos, reports, invoices, etc.) and electronic documents (e.g. electronic mail, fax messages, etc.). Although documents can be transmitted in electronic form, paper documents are still the favorite medium for business communication in the office environment. With the advent of computer technologies, the concept of the "paperless office" evolved and information can be processed and transmitted via computers. To achieve this, it is necessary to handle both the electronic and paper documents in an efficient and integrated way.